GAMMACAL – A USEFUL COMPUTER PROGRAM FOR NEUTRON ACTIVATION ANALYSIS AND RADIOACTIVITY CALCULATIONS - Wasim, M. (The Nucleus, 2010)
GAMMACAL is a computer program with graphical user interface for the calculation of radionuclide activity of gamma emitting radionuclides and elemental concentration using neutron activation analysis data. The software has been tested and is in use for the last ten years. It provides not only concentrations but also quality control data. The program is available for free of cost on writing request to the author.